O ensino de geografia e os estudantes/trabalhadores - uma análise a partir de experiência com EJA em Sapiranga - RS - Alves, Murilo Souto (2009)
The organization of production activities, historically, has several relations which influence the world s socio-spatial design. One of the social groups which are most interested in understanding how such labor relations stipulate our social and spatial condition are the EJA (Education for Youngsters and Adults) students-workers, especially the EJA students from Dr. Décio Gomes Pereira School, located in Sapiranga-RS, which are the target of this work. The active teaching of Geography, focusing this group of people, may help to reveal and contextualize such relations, which contributes to the formation of citizens who are conscious of their socio-spatial reality. To do this, it was necessary a vast theoretical research about labor and the timespace, the economical factors and globalization, historical background of labor and worker s conditions, characterizing the city of Sapiranga-RS aiming to observe how this characterization of labor relations designed and continues to transform the space and the local social condition and, also, the connections existing among labor, education and the teaching of Geography through concepts and methods. Following these steps it was possible to elaborate a course program and also activities to place the Geography teaching into the students reality. The performance and description of the activities show the exchange of knowledge and experience between the teacher and students during class time going beyond the classroom and with influence in the way of thinking, observing and interpreting the world we live in. This reciprocity brought benefits to the teaching/learning relation in the Geography classes for the EJA students/workers, placing the geographical knowledge into the everyday life of these students.